Benefit-confirmation model for post-adoption behavior of mobile instant messaging applications: A comparative analysis of KakaoTalk and Joyn in Korea. Issue 8 (September 2015) - Oghuma, Apollos Patricks; Chang, Younghoon; Libaque-Saenz, Christian Fernando; Park, Myeong-Cheol; Rho, Jae Jeung
Abstract: Facilitated by advancement in technology, today, usage of mobile instant messaging (MIM) applications is a dominant global phenomenon that permeates every part of the world. This phenomenon results in drastic shift in customer attitude and behavior on how to connect and interact with others. MIM service has been replacing telecommunications operators (telcos)׳ short message service, and because third-party MIM applications are those gaining meaningful traction, this trend is threatening the telecommunications industry as it leads to losses in telcos׳ revenues. To cope with this onslaught of third-party MIM applications, telcos launched Joyn, their own MIM application. However, despite their similar technical characteristics, Joyn still lacks user traction. It is critical, therefore, to understand the antecedents to continuance use intention of MIM applications in both contexts. Based on the expanded expectation-confirmation model (ECM), the present research develops a benefit-confirmation model that examines the antecedents to continuance intention to use MIM applications, while provides a comparative analysis of two popular MIM applications in Korea—KakaoTalk (third-party) and Joyn (telcos). A total of 467 data point were collected online. The structural equation modeling results of the total sample provide support for ECM-related hypotheses as well as for significant effects of net benefits and network benefits on continuance intention to use MIM applications, while the comparative analysis suggests that KakaoTalk׳s prominent features are hedonic in nature, whereas, Joyn׳s main attribute is its interoperability. The implications of these findings are discussed. Highlights: We examine drivers of usage intention of mobile instant messaging (MIM) applications. We compare results from KakaoTalk (third-party) and Joyn (telco). Perceived benefits and network benefits play an important role on usage intention. Enjoyment is significant in KakoTalk and network benefits in Joyn. Hedonic features of KakoTalk may be the potential cause of its success.